The Perception of Decision-Making During Patient Care Among Nurse Interns at Umm Al Qura University - Alharbi, Mona; AlQurashi, Nouf; Yehia, Hala (British Journal of Healthcare and Medical Research, 2022)
Aims: The study assesses the perception of decision-making and its effect on the patient are among nurses at Umm-al-Qura University. Backgrounds: The interns who are inducted into the program for a year are included, which leads to the residency program. Methods: The cross-sectional quantitative study is adapted from the sample of (n=30) to the nursing interns in Umm-al-Qura University hospital. The clinical decision- making skills were measured as a part of a questionnaire taken from Wiens (1991) reference article. The methods, such as descriptive statistics, independent t-test, and Cronbach alpha, are utilized for the study. Results: The findings show that the successful integration of the cross-section survey was high, which indicate the high reliability of the results. Among various means for the perceived dimension management received the lowest score in the decision-making; clinical quality is regarded as the highest attribute for dimension with a mean of 4.10, and the lowest dimension is the clinical instructions as a dimension with a 3.3 mean. The percentage distribution according to the perception of stress indicates that there is a 63.3% strong agreement and 36.7% strong disagreement for both the stress that interns feel in the clinical setting. Besides, there was no significant correlation found between decision-making and competence among both males and female interns. Conclusions: The knowledge gathered from the study is beneficial to the nursing staff, interns, administration, and the university authorities to formulate the curriculum based on skill gaps that interns faced during their internship period.